Electric storage device
By using solid graphite as the negative electrode active material layer and controlling the unit opposing area of the positive and negative electrodes, the electrode structure is optimized, solving the problem of difficulty in balancing capacity density and output in the existing technology, and realizing a storage element with high capacity density and large output.
Patent Information
- Application Number
- CN202380043981.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-31
- Filing Date
- 2023-03-30
- Publication Date
- 2025-01-10
AI Technical Summary
While existing energy storage devices can increase capacity density, their output tends to decrease, making it difficult to balance capacity density and output.
Solid graphite is used as the negative electrode active material layer, and the unit opposing area between the positive electrode active material layer and the negative electrode active material layer is controlled to be above 0.59 mAh/cm2 and below 0.90 mAh/cm2. Combined with appropriate porosity and thickness design, the electrode structure is optimized.
It achieves both high output and high capacity density, making it suitable as a power source for hybrid electric vehicles and other applications.
Smart Images

Figure CN119301788A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an electric storage element. Background Art
[0002] Non-aqueous electrolyte secondary batteries represented by lithium ion secondary batteries are widely used in electronic devices such as personal computers and communication terminals, automobiles, etc. due to their high energy density. In addition, as storage elements other than non-aqueous electrolyte secondary batteries, capacitors such as lithium ion capacitors and electric double layer capacitors, and storage elements using electrolytes other than non-aqueous electrolytes are also widely used.
[0003] As a storage element, it is generally provided with an electrode body formed by stacking a positive electrode containing a positive electrode active material and a negative electrode containing a negative electrode active material through a separator. Such an electrode body is contained in a container together with an electrolyte to constitute a storage element. As a negative electrode active material, carbon materials represented by graphite are widely used (see Patent Documents 1 and 2). Prior art literature Patent Literature
[0004] Patent Document 1: Japanese Patent Application Publication No. 2005-222933 Patent Document 2: Japanese Patent Application Publication No. 2017-069039 Summary of the invention Problems to be solved by the invention
[0005] For the storage element, high capacity density and large output are required. As the capacity density, when you want to increase the capacity per unit opposing area of the positive active material layer and the negative active material layer, you can consider thickening the positive active material layer and the negative active material layer, reducing the porosity of the positive active material layer and the negative active material layer, etc. to reduce the opposing area of the positive active material layer and the negative active material layer. However, in the case of such operation, there is a tendency for the resistance of the storage element to increase and the output to decrease. In this way, usually in the storage element, the capacity density and the output are in a relationship of one increasing while the other decreasing, so it is not easy to increase the output while increasing the capacity density.
[0006] An object of the present invention is to provide a power storage element having a large output and achieving both a high capacity density and a large output. Means for solving problems
[0007] An electric storage element according to one aspect of the present invention comprises a positive electrode having a positive electrode active material layer and a negative electrode having a negative electrode active material layer, wherein the rated capacity per unit facing area of the positive electrode active material layer and the negative electrode active material layer is 0.59 mAh / cm 2 Above and 0.90mAh / cm 2 Hereinafter, the negative electrode active material layer includes solid graphite. Effects of the Invention
[0008] According to one aspect of the present invention, it is possible to provide a power storage element having a large output and achieving both a high capacity density and a large output. BRIEF DESCRIPTION OF THE DRAWINGS
[0009] [ Figure 1 ] Figure 1 This is a perspective view showing an embodiment of an electric storage element. [ Figure 2 ] Figure 2 This is a schematic diagram showing one embodiment of an electric storage device constituted by combining a plurality of electric storage elements. DETAILED DESCRIPTION
[0010] First, the outline of the electric storage device disclosed in this specification will be described.
[0011] [1] An electric storage device according to one aspect of the present invention comprises a positive electrode having a positive electrode active material layer and a negative electrode having a negative electrode active material layer, wherein the rated capacity per unit facing area of the positive electrode active material layer and the negative electrode active material layer is 0.59 mAh / cm 2 Above and 0.90mAh / cm 2 Hereinafter, the negative electrode active material layer includes solid graphite.
[0012] The power storage element described in [1] above has a large output and takes into account both high capacity density and large output. The reason for this is not yet certain, but it is speculated to be the following. The rated capacity per unit facing area of the positive electrode active material layer and the negative electrode active material layer in the power storage element described in [1] above (hereinafter also referred to as "capacity density") is 0.59 mAh / cm 2 The capacity density is higher than 0.90 mAh / cm 2 When the positive electrode active material layer and the negative electrode active material layer become thicker, or the porosity of the positive electrode active material layer and the negative electrode active material layer becomes lower, the resistance of the storage element becomes higher and there is a tendency for the output to decrease. In addition, when hollow graphite is used as the negative electrode active material, the electrolyte invades the voids inside the hollow graphite particles, and a high resistance film of the decomposition products of the electrolyte is easily formed until the inside of the particles. In this case, there is also a tendency for the resistance of the storage element to increase and the output to decrease. In contrast, when solid graphite is used as the negative electrode active material, it is difficult to form a high resistance film inside the solid graphite particles, so the high resistance of the storage element can be suppressed, and the output becomes sufficiently large. Based on the above, it is speculated that the storage element described in [1] above has a large output and takes into account both high capacity density and large output.
[0013] [2] In the energy storage device described in [1] above, the average thickness of the negative electrode active material layer may be 20 μm or more and 60 μm or less.
[0014] According to the energy storage element described in [2] above, it is possible to improve capacity density and output in a balanced manner.
[0015] [3] In the energy storage device described in [1] or [2] above, the porosity of the negative electrode active material layer may be 25% or more and 50% or less.
[0016] According to the energy storage element described in [3] above, it is possible to improve capacity density and output in a balanced manner.
[0017] [4] In the storage element described in any one of [1] to [3] above, the facing area of the positive electrode active material layer and the negative electrode active material layer may be 4000 cm 2 Above and 10000cm 2 the following.
[0018] The electric storage device according to the above [4], wherein the facing area of the positive electrode active material layer and the negative electrode active material layer is 4000 cm 2 In addition, by making the facing area of the positive electrode active material layer and the negative electrode active material layer 10000 cm 2 Next, the capacity density can be increased.
[0019] [5] In the energy storage device described in any one of [1] to [4] above, the rated capacity may be 3.7 Ah or more.
[0020] According to the electric storage element described in [5] above, since the capacity is large, the above-mentioned effect can be efficiently exhibited. Therefore, it is particularly suitable as an electric storage element.
[0021] [6] The power storage device described in any one of [1] to [5] above may be used in a hybrid electric vehicle.
[0022] The power storage element described in [6] above has a large output and achieves both high capacity density and high output. Therefore, it is particularly useful as a power source for hybrid electric vehicles that require high capacity density and high output.
[0023] The “facing area of the positive electrode active material layer and the negative electrode active material layer” refers to an area where the positive electrode active material layer and the negative electrode active material layer face each other directly, for example, with a separator interposed therebetween.
[0024] "Rated capacity" refers to the capacity (Ah) used for the capacity display of the storage element. That is, the "rated capacity" is the capacity displayed in the storage element and the instruction manual, specification sheet, catalog, etc. attached to the storage element. It should be noted that when the rated capacity is expressed in the form of energy in "kWh", the rated capacity (Ah) can be calculated by dividing by the nominal voltage. Here, "nominal voltage" refers to the voltage (V) used for the voltage display of the storage element. That is, the "nominal voltage" is the voltage displayed in the storage element and the instruction manual, specification sheet, catalog, etc. attached to the storage element.
[0025] “Graphite” refers to the average lattice spacing (d) of the (002) plane determined by X-ray diffraction before charge or discharge or in the discharged state. 002 ) is a carbon material having a diameter of 0.33 nm or more and less than 0.34 nm. Here, the "discharge state" of the carbon material refers to a state of discharge in which the charge transport ions that can be absorbed and released accompanying the charge and discharge are fully released from the carbon material as the negative electrode active material. For example, in a half-cell in which the negative electrode containing the carbon material as the negative electrode active material is used as the working electrode and the metal Li is used as the counter electrode, it is a state in which the open circuit voltage is 0.7 V or more.
[0026] The "solid" in solid graphite means that the inside of the graphite particles is filled and there are substantially no voids. More specifically, "solid" means that in the cross-section of the particles observed in the SEM image obtained using a scanning electron microscope (SEM), the area ratio of the voids in the particles relative to the area of the entire particle (void ratio) is 2% or less. In a preferred embodiment, the area ratio of the above-mentioned voids in solid graphite can be 1% or less, or 0.7% or less, or 0.5% or less. The lower limit of the area ratio (void ratio) can be 0%. The "area ratio of voids within the particle to the area of the entire particle (void ratio)" in the graphite particle can be determined by the following procedure. (1) Preparation of test samples The negative electrode to be measured is fixed with a thermosetting resin. For the negative electrode fixed with the resin, the cross section is exposed by using a cross-section polisher to prepare a sample for measurement. It should be noted that the negative electrode to be measured is prepared by the following steps. In the case where the negative electrode before assembling the storage element can be prepared, it is used directly. In the case of preparing from the assembled storage element, the storage element is first discharged at a constant current of 0.1C to the discharge termination voltage during normal use to obtain a discharged state. The storage element in the discharged state is disassembled, the negative electrode is taken out, and after being thoroughly cleaned with dimethyl carbonate, it is dried under reduced pressure at room temperature for 24 hours. The operations from disassembly of the storage element to preparation of the negative electrode to be measured are carried out in a dry air atmosphere with a dew point below -40°C. “In normal use” means a case where the energy storage element is used under the charge and discharge conditions recommended or specified for the energy storage element. When a device for using the energy storage element is prepared, it means a case where the energy storage element is used using the device. (2) Acquisition of SEM images In obtaining the SEM image, JSM-7001F (manufactured by JEOL Ltd.) is used as SEM. The SEM image is an image of observing a secondary electron image. The accelerating voltage is set to 15 kV. The observation magnification is set to a magnification of more than 3 and less than 15 graphite particles appearing in one field of view. The obtained SEM image is saved as an image file. In addition, each condition such as spot diameter, working distance, irradiation current, brightness, focus, etc. is appropriately set in a manner such that the outline of the graphite particles becomes clear. (3) Cutting the outline of graphite particles The image clipping function of the image editing software Adobe Photoshop Elements 11 was used to clip the outline of the graphite particles from the obtained SEM image. The clipping of the outline was performed by selecting the outside of the outline of the graphite particles using the quick selection tool and editing the outside of the graphite particles to a black background. At this time, if the number of graphite particles with successfully clipped outlines was less than 3, the SEM image was obtained again until the number of graphite particles with successfully clipped outlines became more than 3. (4) Binarization The image of the first graphite particle among the cut graphite particles was binarized using the image analysis software PopImaging 6.00, with a concentration 20% lower than the concentration at the maximum intensity set as a threshold. The area on the side with a higher concentration was calculated by binarization, and this was used as the "area S1 of the voids within the particle". Next, the same first graphite particle image as before was binarized with a concentration of 10% as a threshold value. The outer edge of the graphite particle was determined by binarization, and the area inside the outer edge was calculated as the "area S0 of the entire particle". The ratio of S1 to S0 (S1 / S0) is calculated using S1 and S0 calculated above, thereby calculating the "area ratio R1 of the voids within the particle to the area of the entire particle" in the first graphite particle. The above binarization process is also performed on the images of the second and subsequent graphite particles among the cut graphite particles to calculate the areas S1 and S0. Based on the calculated areas S1 and S0, the area ratios R2, R3, ... of the voids of each graphite particle are calculated. (5) Determination of the area ratio of voids By calculating the average of the area ratios R1, R2, R3, ... of all the voids calculated by the binarization process, "the area ratio of the voids in the particle to the area of the entire particle (void ratio)" is determined. In addition, instead of the scanning electron microscope used in the above-mentioned "obtaining the SEM image", the image editing software used in the "trimming of the outline of the graphite particles", and the image analysis software used in the "binarization processing", it is also possible to use a device and software that can perform the same measurements, image editing, and image analysis as them.
[0027] The storage element, storage device, storage element manufacturing method and other embodiments of one embodiment of the present invention are described in detail. It should be noted that the names of the components (components) used in each embodiment are sometimes different from the names of the components (components) used in the background art.
[0028] <Electrical storage element> The storage element of one embodiment of the present invention comprises: an electrode body having a positive electrode, a negative electrode and a separator; an electrolyte; and a container for accommodating the electrode body and the electrolyte. The electrode body is generally a stacked type in which a plurality of positive electrodes and a plurality of negative electrodes are stacked with a separator between them, or a wound type in which a positive electrode and a negative electrode are wound with a separator between them. The positive electrode has a positive electrode active material layer, and the negative electrode has a negative electrode active material layer. In one embodiment of the present invention, the positive electrode active material layer and the negative electrode active material layer constitute the electrode body in a state in which they are opposed to each other with a separator between them. There may also be a portion in which the positive electrode active material layer and the negative electrode active material layer are not opposed to each other. The electrolyte exists in a state impregnated in the positive electrode, the negative electrode and the separator. As an example of a storage element, a non-aqueous electrolyte secondary battery (hereinafter also referred to as a "secondary battery") using a non-aqueous electrolyte as an electrolyte is described.
[0029] (positive electrode) The positive electrode includes a positive electrode substrate and a positive electrode active material layer disposed on the positive electrode substrate directly or via an intermediate layer.
[0030] The positive electrode substrate has electrical conductivity. Whether it has "electrical conductivity" is determined by measuring the volume resistivity of 10 -2Ω·cm is used as a threshold value for determination. As the material of the positive electrode substrate, metals such as aluminum, titanium, tantalum, stainless steel, or their alloys can be used. Among them, from the viewpoints of potential resistance, high conductivity and cost, aluminum or aluminum alloys are preferred. As the positive electrode substrate, foil, vapor-deposited film, mesh, porous material, etc. can be cited. From the viewpoint of cost, foil is preferred. Therefore, as the positive electrode substrate, aluminum foil or aluminum alloy foil is preferred. As aluminum or aluminum alloy, A1085, A3003, A1N30, etc. specified in JIS-H-4000 (2014) or JIS-H-4160 (2006) can be exemplified.
[0031] The average thickness of the positive electrode substrate is preferably 3 μm or more and 50 μm or less, more preferably 5 μm or more and 40 μm or less, further preferably 8 μm or more and 30 μm or less, and particularly preferably 10 μm or more and 25 μm or less. By setting the average thickness of the positive electrode substrate to the above range, the strength of the positive electrode substrate can be improved, and the energy density per unit volume of the storage element can be improved. The "average thickness" of the positive electrode substrate and the negative electrode substrate described later refers to the value obtained by dividing the punching mass when punching a substrate of a specified area by the true density of the substrate and the punching area.
[0032] The intermediate layer is a layer disposed between the positive electrode substrate and the positive electrode active material layer. The intermediate layer reduces the contact resistance between the positive electrode substrate and the positive electrode active material layer by including a conductive agent such as carbon particles. The composition of the intermediate layer is not particularly limited, and for example, includes a binder and a conductive agent.
[0033] The positive electrode active material layer contains a positive electrode active material and may contain any component such as a conductive agent, a binder, a thickener, and a filler as required.
[0034] As the positive electrode active material, it can be appropriately selected from known positive electrode active materials. As the positive electrode active material for lithium ion secondary batteries, materials that can absorb and release lithium ions are generally used. As the positive electrode active material, for example, lithium transition metal composite oxides having an α-NaFeO2 type crystal structure, lithium transition metal composite oxides having a spinel type crystal structure, polyanion compounds, chalcogen compounds, sulfur, etc. can be cited. As the lithium transition metal composite oxide having an α-NaFeO2 type crystal structure, for example, Li[Li x Ni (1-x) ]O2(0≤x<0.5), Li[Li x Ni γ Co (1-x-γ) ]O2(0≤x<0.5, 0<γ<1, 0<1-x-γ), Li[Li x Co (1-x) ]O2(0≤x<0.5), Li[Li x Ni γMn (1-x-γ) ]O2(0≤x<0.5, 0<γ<1, 0<1-x-γ), Li[Li x Ni γ Mn β Co (1-x-γ-β) ]O2(0≤x<0.5, 0<γ, 0<β, 0.5<γ+β<1, 0<1-x-γ-β), Li[Li x Ni γ Co β Al (1-x-γ-β) ]O2 (0≤x<0.5, 0<γ, 0<β, 0.5<γ+β<1, 0<1-x-γ-β), etc. As lithium transition metal composite oxides having a spinel crystal structure, Li x Mn2O4、Li x Ni γ Mn (2-γ) O4, etc. As polyanion compounds, LiFePO4, LiMnPO4, LiNiPO4, LiCoPO4, Li3V2(PO4)3, Li2MnSiO4, Li2CoPO4F, etc. can be mentioned. As chalcogen compounds, titanium disulfide, molybdenum disulfide, molybdenum dioxide, etc. can be mentioned. Atoms or part of polyanions in these materials can be replaced by atoms or anions composed of other elements. The surfaces of these materials can also be coated with other materials. In the positive electrode active material layer, one of these materials can be used alone, or two or more can be mixed and used.
[0035] The positive electrode active material is usually a particle (powder). The average particle size of the positive electrode active material is preferably set to 0.1 μm or more and 20 μm or less, for example. By making the average particle size of the positive electrode active material above the above lower limit, the manufacture or processing of the positive electrode active material becomes easy. By making the average particle size of the positive electrode active material below the above upper limit, the electronic conductivity of the positive electrode active material layer is improved. It should be noted that when a composite of the positive electrode active material and other materials is used, the average particle size of the composite is used as the average particle size of the positive electrode active material. "Average particle size" refers to the value when the volume-based cumulative distribution calculated in accordance with JIS-Z-8819-2 (2001) is 50%, based on the particle size distribution measured by the laser diffraction-scattering method of the diluted solution obtained by diluting the particles with a solvent in accordance with JIS-Z-8825 (2013).
[0036] In order to obtain a powder with a predetermined particle size, a pulverizer, a classifier, etc. can be used. As a pulverization method, for example, a method using a mortar, a ball mill, a sand mill, a vibrating ball mill, a planetary ball mill, a jet mill, a reverse jet mill, a rotating airflow type jet mill, or a sieve can be cited. When pulverizing, wet pulverization in which an organic solvent such as water or hexane coexists can also be used. As a classification method, a sieve, a pneumatic classifier, etc. can be used as needed in a dry or wet method.
[0037] The content of the positive electrode active material in the positive electrode active material layer is preferably 50 mass % or more and 99 mass % or less, more preferably 70 mass % or more and 98 mass % or less, further preferably 80 mass % or more and 95 mass % or less. By setting the content of the positive electrode active material to the above range, it is possible to take into account the high energy density and manufacturability of the positive electrode active material layer.
[0038] The conductive agent is not particularly limited as long as it is a material with conductivity. As such a conductive agent, for example, carbonaceous materials, metals, conductive ceramics, etc. can be mentioned. As carbonaceous materials, graphite, non-graphite carbon, graphene-based carbon, etc. can be mentioned. As non-graphite carbon, carbon nanofibers, pitch-based carbon fibers, carbon black, etc. can be mentioned. As carbon black, furnace black, acetylene black, Ketjen black, etc. can be mentioned. As graphene-based carbon, graphene, carbon nanotubes (CNT), fullerene, etc. can be mentioned. As the shape of the conductive agent, powder, fiber, etc. can be mentioned. As the conductive agent, one of these materials can be used alone, or two or more can be mixed and used. In addition, these materials can also be used in a composite. For example, a material in which carbon black and CNT are composited can also be used. Among them, from the viewpoint of electronic conductivity and coating properties, carbon black is preferred, and acetylene black is preferred.
[0039] The content of the conductive agent in the positive electrode active material layer is preferably 1 mass % to 10 mass %, more preferably 3 mass % to 9 mass %. By setting the content of the conductive agent in the above range, the energy density of the storage element can be increased.
[0040] As adhesives, for example, there can be mentioned thermoplastic resins such as fluororesins (polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), etc.), polyethylene, polypropylene, polyacrylic acid, polyimide, etc.; elastomers such as ethylene-propylene-diene rubber (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, etc.; polysaccharide polymers, etc.
[0041] The content of the binder in the positive electrode active material layer is preferably 1% by mass or more and 10% by mass or less, and more preferably 3% by mass or more and 9% by mass or less. By setting the content of the binder within the above range, the positive electrode active material can be stably retained.
[0042] As the thickener, for example, polysaccharide polymers such as carboxymethyl cellulose (CMC) and methyl cellulose can be cited. When the thickener has a functional group that reacts with lithium or the like, the functional group can be deactivated in advance by methylation or the like. In the case where the positive electrode active material layer contains a thickener, the content of the thickener in the positive electrode active material layer can be set to, for example, 0.1% by mass or more and 10% by mass or less. The content of the thickener in the positive electrode active material layer can be 5% by mass or less, 1% by mass or less, or 0% by mass.
[0043] Filler is not particularly limited. As filler, polyolefins such as polypropylene and polyethylene, silica, aluminum oxide, titanium dioxide, calcium oxide, strontium oxide, barium oxide, magnesium oxide, inorganic oxides such as aluminosilicate, hydroxides such as magnesium hydroxide, calcium hydroxide, aluminum hydroxide, carbonates such as calcium carbonate, calcium fluoride, barium fluoride, barium sulfate and other insoluble ionic crystals, nitrides such as aluminum nitride and silicon nitride, talc, montmorillonite, boehmite, zeolite, apatite, kaolin, mullite, spinel, olivine, sericite, bentonite, mica and other materials from mineral resources or their man-made products can be cited. In the case where the positive electrode active material layer contains filler, the content of the filler in the positive electrode active material layer can be, for example, set to 0.1% by mass or more and 10% by mass or less. The content of the filler in the positive electrode active material layer can be 5% by mass or less, 1% by mass or less, or 0% by mass.
[0044] The positive electrode active material layer may also contain typical non-metallic elements such as B, N, P, F, Cl, Br, I, typical metal elements such as Li, Na, Mg, Al, K, Ca, Zn, Ga, Ge, Sn, Sr, Ba, and transition metal elements such as Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Mo, Zr, Nb, and W as components other than the positive electrode active material, conductive agent, binder, thickener, and filler.
[0045] The average thickness of the positive electrode active material layer is preferably 15 μm or more and 50 μm or less, more preferably 20 μm or more and 45 μm or less, and further preferably 25 μm or more and 40 μm or less. When the average thickness of the positive electrode active material layer is within the above range, the capacity density and output can be improved more evenly. The average thickness of the positive electrode active material layer and the negative electrode active material layer described later is set to the average value of the thickness measured at any 5 points. The average thickness of the above-mentioned positive electrode active material layer is the average thickness of each layer of the positive electrode active material layer. In the case where positive electrode active material layers are respectively provided on both sides of the positive electrode substrate, it is the average thickness of each positive electrode active material layer. The average thickness of the negative electrode active material layer described later is also the same.
[0046] The porosity of the positive electrode active material layer is preferably 35% or more and 47% or less, and more preferably 37% or more and 45% or less. When the porosity of the positive electrode active material layer is within the above range, the capacity density and output can be improved more evenly. The porosity of the positive electrode active material layer refers to the value obtained by the following formula based on the true density of the positive electrode active material layer calculated from the true density of each component constituting the positive electrode active material layer and the apparent density of the positive electrode active material layer. Porosity (%) = 100 - (apparent density / true density) × 100 The apparent density of the positive electrode active material layer is the value obtained by dividing the mass of the positive electrode active material layer by the apparent volume of the positive electrode active material layer. The apparent volume is the volume including the voids and can be obtained as the product of the average thickness and area of the positive electrode active material layer.
[0047] The preparation of the positive electrode can be carried out, for example, by applying a positive electrode mixture paste directly or through an intermediate layer on the positive electrode substrate and drying it. After drying, pressing can be performed as needed. The positive electrode mixture paste contains the positive electrode active material and the conductive agent, binder and other components constituting the positive electrode active material layer as arbitrary components. The positive electrode mixture paste usually also contains a dispersion medium.
[0048] (negative electrode) The negative electrode comprises a negative electrode substrate and a negative electrode active material layer disposed on the negative electrode substrate directly or via an intermediate layer. The structure of the intermediate layer is not particularly limited, and can be selected from the structures exemplified for the positive electrode described above.
[0049] The negative electrode substrate has conductivity. As the material of the negative electrode substrate, metals such as copper, nickel, stainless steel, nickel-plated steel, or their alloys, carbonaceous materials, etc. can be used. Among them, copper or copper alloys are preferred. As the negative electrode substrate, foil, vapor-deposited film, mesh, porous material, etc. can be cited. From the perspective of cost, foil is preferred. Therefore, as the negative electrode substrate, copper foil or copper alloy foil is preferred. As examples of copper foil, rolled copper foil, electrolytic copper foil, etc. can be cited.
[0050] The average thickness of the negative electrode substrate is preferably 2 μm or more and 35 μm or less, more preferably 3 μm or more and 30 μm or less, further preferably 4 μm or more and 25 μm or less, and particularly preferably 5 μm or more and 20 μm or less. By setting the average thickness of the negative electrode substrate to the above range, the strength of the negative electrode substrate can be increased, and the energy density per unit volume of the storage element can be increased.
[0051] The negative electrode active material layer contains a negative electrode active material. The negative electrode active material layer contains any component such as a conductive agent, a binder, a thickener, and a filler as needed. The conductive agent, the binder, the thickener, the filler, and any component can be selected from the materials exemplified for the positive electrode.
[0052] The negative electrode active material includes solid graphite. By including solid graphite in the negative electrode active material of the negative electrode, the output of the storage element can be increased. Solid graphite can be artificial graphite or natural graphite. Artificial graphite is a general term for artificially manufactured graphite, and natural graphite is a general term for graphite collected from natural minerals. As natural graphite, specifically, flaky graphite (scaly graphite), blocky graphite, earthy graphite, etc. can be exemplified. Solid graphite can be flat flaky natural graphite, or spheroidized natural graphite obtained by spheroidizing the flaky graphite. Solid graphite can also be graphite particles with a coating (e.g., amorphous carbon coating) applied on the surface.
[0053] Solid graphite is sometimes preferably natural graphite (solid natural graphite). In the X-ray diffraction pattern of natural graphite measured using CuKα rays before charge and discharge or in the discharge state, four peaks may appear in the range of diffraction angle 2θ of 40° to 50°. These four peaks are considered to be two peaks from the structure of the hexagonal crystal system and two peaks from the structure of the rhombohedral crystal system. In the case of artificial graphite, generally only two peaks from the structure of the hexagonal crystal system appear. In the X-ray diffraction pattern, the ratio of the peak intensity from the (012) plane to the peak intensity from the (100) plane ((012) / (100)) is preferably 0.3 or more, and more preferably 0.4 or more. The above peak intensity ratio ((012) / (100)) is preferably 0.6 or less. Here, the (100) plane is from the structure of the hexagonal crystal system, and the (012) plane is from the structure of the rhombohedral crystal system.
[0054] The average particle size of solid graphite is, for example, preferably 1 μm or more and 100 μm or less, more preferably 2 μm or more and 50 μm or less, further preferably 3 μm or more and 30 μm or less, and further preferably 5 μm or more and 20 μm or less. By making the average particle size of solid graphite above the above lower limit, the manufacture or processing of solid graphite becomes easy. By making the average particle size of solid graphite below the above upper limit, there is a tendency that the electronic conductivity of the negative electrode active material layer is improved and the output of the storage element becomes larger. In addition, by making the average particle size of solid graphite below the above upper limit, there is a tendency that the negative electrode active material layer is densified and the energy density of the storage element is also improved. In order to obtain solid graphite with a specified particle size, a pulverizer, a classifier, etc. can be used. The pulverization method and the classification method can be selected from the methods exemplified by the above-mentioned positive electrode, for example.
[0055] As the aspect ratio of solid graphite, it is preferably greater than 1 and less than 5, more preferably greater than 1.5 and less than 4, and further preferably greater than 2 and less than 3. When the aspect ratio of solid graphite is within the above range, there is a tendency that the resistance of the negative electrode active material layer becomes sufficiently low and the output of the storage element becomes larger. In addition, when the aspect ratio of solid graphite is within the above range, there is a tendency that the negative electrode active material layer is densified and the energy density of the storage element is also improved. The aspect ratio refers to the ratio (A / B) of the longest diameter A of the particle to the longest diameter B in the direction perpendicular to the diameter A in the cross section of the particle observed in the SEM image obtained using SEM. The SEM image for calculating the aspect ratio can be obtained by the same method as the case of calculating the area ratio (void ratio) of the voids within the particles in the above-mentioned graphite particles relative to the area of the entire particle.
[0056] The content of solid graphite in the negative electrode active material layer is preferably 60% by mass or more and 99% by mass or less, more preferably 90% by mass or more and 98% by mass or less, and sometimes more preferably 95% by mass or more, 97% by mass or more, or 98% by mass or more. By setting the content of solid graphite to the above range, the output of the storage element can be further increased.
[0057] The negative electrode active material may also contain other negative electrode active materials other than solid graphite. Examples of other negative electrode active materials include: metal Li; metals or semimetals such as Si and Sn; metal oxides or semimetal oxides such as Si oxide, Ti oxide, and Sn oxide; Li4Ti5O 12 、LiTiO 2、 Titanium-containing oxides such as TiNb2O7; polyphosphate compounds; silicon carbide; carbon materials such as graphite other than solid graphite, non-graphite carbon (graphitizable carbon or non-graphitizable carbon), etc. Among them, the content ratio of solid graphite relative to the total negative electrode active material is preferably 80% by mass or more, more preferably 90% by mass or more, further preferably 99% by mass or more, further preferably 99.9% by mass or more, and particularly preferably 100% by mass. In this way, when the negative electrode active material is essentially composed only of solid graphite, the output of the storage element can be further increased.
[0058] “Non-graphite carbon” refers to the average lattice spacing (d ) of the (002) plane determined by X-ray diffraction before charge / discharge or in a discharged state. 002 ) is a carbon material having a diameter of 0.34 nm or more and 0.42 nm or less. Examples of non-graphite carbon include difficult-graphitization carbon and easy-graphitization carbon. Examples of non-graphite carbon include materials derived from resins, petroleum asphalt or materials derived from petroleum asphalt, petroleum coke or materials derived from petroleum coke, materials derived from plants, materials derived from alcohols, and the like.
[0059] "Non-graphitizable carbon" refers to the above-mentioned 002 A carbon material having a diameter of 0.36 nm or more and 0.42 nm or less.
[0060] "Graphitizable carbon" refers to the above-mentioned 002 A carbon material having a diameter of 0.34 nm or more and less than 0.36 nm.
[0061] The content of all negative electrode active materials in the negative electrode active material layer is preferably 60 mass % or more and 99 mass % or less, more preferably 90 mass % or more and 98 mass % or less, and sometimes further preferably 95 mass %, 97 mass % or more or 98 mass % or more. By setting the content of the negative electrode active material to the above range, it is possible to take into account the high energy density and manufacturability of the negative electrode active material layer.
[0062] When the negative electrode active material layer contains a conductive agent, the content of the conductive agent in the negative electrode active material layer can be, for example, 1% by mass or more and 10% by mass or less. The content of the conductive agent in the negative electrode active material layer is preferably 5% by mass or less, and sometimes more preferably 2% by mass or less, 1% by mass or less, 0.1% by mass or less, or 0% by mass. When the content of the conductive agent in the negative electrode active material layer is small or does not contain a conductive agent, the content of the negative electrode active material can be increased, and the energy density of the storage element can be improved.
[0063] The content of the binder in the negative electrode active material layer is preferably 0.1% by mass or more and 10% by mass or less, and more preferably 1% by mass or more and 5% by mass or less. By setting the content of the binder within the above range, the negative electrode active material can be stably retained.
[0064] The content of the thickener in the negative electrode active material layer is preferably 0.1% by mass or more and 5% by mass or less, and more preferably 0.5% by mass or more and 2% by mass or less.
[0065] When the negative electrode active material layer contains fillers, the content of the fillers in the negative electrode active material layer can be set to, for example, 0.1% by mass or more and 10% by mass or less. The content of the fillers in the negative electrode active material layer can be 5% by mass or less, 1% by mass or less, or 0% by mass. When the content of the fillers in the negative electrode active material layer is small or does not contain fillers, the content of the negative electrode active material can be increased, and the energy density of the storage element can be improved.
[0066] The negative electrode active material layer may also contain typical non-metallic elements such as B, N, P, F, Cl, Br, I, typical metal elements such as Li, Na, Mg, Al, K, Ca, Zn, Ga, Ge, Sn, Sr, Ba, and transition metal elements such as Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Mo, Zr, Ta, Hf, Nb, and W as components other than the negative electrode active material, conductive agent, binder, thickener, and filler.
[0067] The average thickness of the negative electrode active material layer is preferably 20 μm to 60 μm, more preferably 25 μm to 55 μm, and further preferably 30 μm to 50 μm. When the average thickness of the negative electrode active material layer is within the above range, the capacity density and output can be improved in a more balanced manner.
[0068] The porosity of the negative electrode active material layer is preferably 25% or more and 50% or less, and more preferably 30% or more and 45% or less. When the porosity of the negative electrode active material layer is within the above range, the capacity density and output can be improved more evenly. The porosity of the negative electrode active material layer can be obtained by the same method as the porosity of the positive electrode active material layer.
[0069] The production of the negative electrode can be carried out, for example, by applying a negative electrode mixture paste directly or through an intermediate layer on the negative electrode substrate and drying it. After drying, pressing can be performed as needed. The negative electrode mixture paste contains a negative electrode active material containing solid graphite and various components constituting the negative electrode active material layer such as a conductive agent and a binder as arbitrary components. The negative electrode mixture paste usually also contains a dispersion medium.
[0070] (Diaphragm) The separator can be appropriately selected from known separators. As the separator, for example, a separator consisting only of a substrate layer, a separator having a heat-resistant layer containing heat-resistant particles and a binder formed on one or both sides of the substrate layer, etc. can be used. As the shape of the substrate layer of the separator, for example, woven fabrics, non-woven fabrics, porous resin films, etc. can be cited. Among these shapes, porous resin films are preferred from the viewpoint of strength, and non-woven fabrics are preferred from the viewpoint of liquid retention of non-aqueous electrolytes. As the material of the substrate layer of the separator, from the viewpoint of shutdown function, polyolefins such as polyethylene and polypropylene are preferred, and from the viewpoint of resistance to oxidative decomposition, for example, polyimides, aromatic polyamides, etc. are preferred. As the substrate layer of the separator, a material composited with these resins can also be used.
[0071] The heat-resistant particles contained in the heat-resistant layer preferably have a mass reduction of 5% or less when the temperature is raised from room temperature to 500°C in an air atmosphere of 1 atmosphere, and more preferably have a mass reduction of 5% or less when the temperature is raised from room temperature to 800°C. As materials whose mass reduction is less than the prescribed value, inorganic compounds can be cited. As inorganic compounds, for example, oxides such as iron oxide, silicon oxide, aluminum oxide, titanium oxide, zirconium oxide, calcium oxide, strontium oxide, barium oxide, magnesium oxide, and aluminum silicate; nitrides such as aluminum nitride and silicon nitride; carbonates such as calcium carbonate; sulfates such as barium sulfate; insoluble ionic crystals such as calcium fluoride, barium fluoride, and barium titanate; covalently bonded crystals such as silicon and diamond; talc, montmorillonite, boehmite, zeolite, apatite, kaolin, mullite, spinel, olivine, sericite, bentonite, mica, and other mineral resources or their artificial products. As inorganic compounds, monomers or composites of these substances can be used alone, or two or more can be mixed and used. Among these inorganic compounds, silicon oxide, aluminum oxide, or aluminosilicate is preferred from the viewpoint of safety of the electric storage element.
[0072] The porosity of the separator is preferably 80% by volume or less from the viewpoint of strength, and preferably 20% by volume or more from the viewpoint of discharge performance. Here, the “porosity” is a value based on volume, and refers to a value measured by a mercury porosimeter.
[0073] As a separator, a polymer gel composed of a polymer and a non-aqueous electrolyte can be used. As a polymer, for example, polyacrylonitrile, polyethylene oxide, polypropylene oxide, polymethyl methacrylate, polyvinyl acetate, polyvinyl pyrrolidone, polyvinylidene fluoride, etc. can be cited. If a polymer gel is used, it has an effect of suppressing leakage. As a separator, a porous resin film or a nonwoven fabric as described above can be used together with a polymer gel.
[0074] (Non-aqueous electrolyte) The non-aqueous electrolyte can be appropriately selected from known non-aqueous electrolytes. A non-aqueous electrolyte solution can be used. The non-aqueous electrolyte solution contains a non-aqueous solvent and an electrolyte salt dissolved in the non-aqueous solvent.
[0075] As nonaqueous solvent, it can be suitably selected from known nonaqueous solvents. As nonaqueous solvent, cyclic carbonate, linear carbonate, carboxylate, phosphoric acid ester, sulfonic acid ester, ether, amides, nitrile etc. can be enumerated. As nonaqueous solvent, it can be used that the part of hydrogen atom contained in these compounds is replaced by halogen.
[0076] Examples of the cyclic carbonate include ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), vinylene carbonate (VC), vinyl ethylene carbonate (VEC), chloroethylene carbonate, fluoroethylene carbonate (FEC), difluoroethylene carbonate (DFEC), styrene carbonate, 1-phenylvinylene carbonate, 1,2-diphenylvinylene carbonate, etc. Among them, EC is preferred.
[0077] Examples of the chain carbonate include diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diphenyl carbonate, trifluoroethyl methyl carbonate, bis(trifluoroethyl) carbonate, etc. Among them, EMC is preferred.
[0078] As nonaqueous solvent, preferably use cyclic carbonate or linear carbonate, more preferably use cyclic carbonate and linear carbonate.By using cyclic carbonate, can promote the dissociation of electrolyte salt and improve the ionic conductivity of nonaqueous electrolyte.By using linear carbonate, can suppress the viscosity of nonaqueous electrolyte to be lower.When using cyclic carbonate and linear carbonate, as the volume ratio (cyclic carbonate: linear carbonate) of cyclic carbonate and linear carbonate, for example, preferably be set to the scope of 5:95 to 50:50.
[0079] The electrolyte salt may be appropriately selected from known electrolyte salts. Examples of the electrolyte salt include lithium salts, sodium salts, potassium salts, magnesium salts, and onium salts. Among them, lithium salts are preferred.
[0080] As lithium salts, inorganic lithium salts such as LiPF6, LiPO2F2, LiBF4, LiClO4, and LiN(SO2F)2, lithium oxalate salts such as lithium bis(oxalate)borate (LiBOB), lithium difluorooxalateborate (LiFOB), and lithium bis(oxalate)difluorophosphate (LiFOP), and lithium salts having halogenated hydrocarbon groups such as LiSO3CF3, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiN(SO2CF3)(SO2C4F9), LiC(SO2CF3)3, and LiC(SO2C2F5)3 can be cited. Among them, inorganic lithium salts are preferred, and LiPF6 is more preferred.
[0081] The content of the electrolyte salt in the non-aqueous electrolyte is preferably 0.1 mol / dm 3 Above and 2.5 mol / dm 3 Below, more preferably 0.3 mol / dm 3 Above and 2.0 mol / dm 3 Below, more preferably 0.5 mol / dm 3 Above 1.7 mol / dm 3Below, particularly preferably 0.7 mol / dm 3 Above and 1.5 mol / dm 3 By setting the content of the electrolyte salt to the above range, the ion conductivity of the non-aqueous electrolyte can be improved.
[0082] In addition to the non-aqueous solvent and the electrolyte salt, the non-aqueous electrolyte may also contain additives. Examples of additives include halogenated carbonates such as fluoroethylene carbonate (FEC) and difluoroethylene carbonate (DFEC); oxalates such as lithium bis(oxalato)borate (LiBOB), lithium difluorooxalatoborate (LiFOB), and lithium bis(oxalate)difluorophosphate (LiFOP); imide salts such as lithium bis(fluorosulfonyl)imide (LiFSI); biphenyl, alkylbiphenyl, terphenyl, partial hydride of terphenyl, cyclohexylbenzene, Aromatic compounds such as tert-butylbenzene, tert-amylbenzene, diphenyl ether, dibenzofuran, etc.; halides of the above aromatic compounds such as 2-fluorobiphenyl, o-cyclohexylfluorobenzene, p-cyclohexylfluorobenzene, etc.; halogenated anisole compounds such as 2,4-difluoroanisole, 2,5-difluoroanisole, 2,6-difluoroanisole, 3,5-difluoroanisole, etc.; vinylene carbonate, methyl vinylene carbonate, ethyl vinylene carbonate, succinic anhydride, glutaric anhydride, malic anhydride anhydride, citraconic anhydride, glutaric anhydride, itaconic anhydride, cyclohexanedicarboxylic anhydride; ethylene sulfite, propylene sulfite, dimethyl sulfite, methyl methanesulfonate, busulfan, methyl toluenesulfonate, dimethyl sulfate, ethylene sulfate, cyclopentane, dimethyl sulfone, diethyl sulfone, dimethyl sulfoxide, diethyl sulfoxide, tetramethylene sulfoxide, diphenyl sulfide, 4,4'-bis(2,2-dioxo-1,3,2-dioxathiapentane), 4-methyl Sulfonyloxymethyl-2,2-dioxo-1,3,2-dioxathiapentane, thioanisole, diphenyl disulfide, dipyridinium disulfide, 1,3-propylene sultone, 1,3-propane sultone, 1,4-butane sultone, 1,4-butene sultone, perfluorooctane, tris(trimethylsilyl)borate, tris(trimethylsilyl)phosphate, tetrakis(trimethylsilyl)titanate, monofluorolithium phosphate, difluorolithium phosphate, etc. These additives may be used alone or in combination of two or more.
[0083] The content of the additive contained in the nonaqueous electrolyte is preferably 0.01% by mass and 10% by mass relative to the overall mass of the nonaqueous electrolyte, more preferably 0.1% by mass and 7% by mass, further preferably 0.2% by mass and 5% by mass, particularly preferably 0.3% by mass and 3% by mass. By setting the content of the additive to the above range, it is possible to improve the capacity maintenance performance or cycle performance after high temperature storage, or further improve safety.
[0084] A solid electrolyte may be used as the non-aqueous electrolyte, or a non-aqueous electrolyte solution and a solid electrolyte may be used in combination.
[0085] The solid electrolyte can be selected from any material that has ion conductivity and is solid at room temperature (e.g., 15° C. to 25° C.), such as lithium, sodium, and calcium. Examples of the solid electrolyte include sulfide solid electrolytes, oxide solid electrolytes, nitride solid electrolytes, and polymer solid electrolytes.
[0086] In the case of lithium ion secondary batteries, examples of sulfide solid electrolytes include Li2S-P2S5, LiI-Li2S-P2S5, Li 10 Ge-P2S 12 wait.
[0087] (rated capacity, purpose, etc.) The rated capacity per unit facing area of the positive electrode active material layer and the negative electrode active material layer of the electric storage element according to one embodiment of the present invention, that is, the capacity density is 0.59 mAh / cm 2 Above and 0.90mAh / cm 2 The lower limit of the capacity density is preferably 0.60 mAh / cm 2 、0.65mAh / cm 2 、0.70mAh / cm 2 or 0.75mAh / cm 2 By making the capacity density above the lower limit, the energy density of the storage element is improved. On the other hand, the upper limit of the capacity density is preferably 0.85 mAh / cm 2 、0.80mAh / cm 2 、0.75mAh / cm 2 or 0.70mAh / cm 2 By setting the capacity density to be equal to or less than the upper limit, the output of the energy storage element increases.
[0088] The rated capacity of the storage element as one embodiment of the present invention is preferably 3.7Ah or more and 10Ah or less. As the lower limit of the above-mentioned rated capacity, it is sometimes more preferably 3.8Ah, 3.9Ah, 4.0Ah, 4.1Ah or 4.2Ah. The storage element is particularly suitable as such a storage element with a large rated capacity. The upper limit of the above-mentioned rated capacity can be 9Ah, 8Ah, 7Ah, 6Ah, 5Ah, 4.5Ah, 4.3Ah, 4.2Ah, 4.1Ah or 4.0Ah.
[0089] The facing area of the positive electrode active material layer and the negative electrode active material layer of the electric storage element as one embodiment of the present invention is preferably 4000 cm 2Above and 10000cm 2 The lower limit of the above-mentioned facing area is sometimes more preferably 4500cm 2 、5000cm 2 、5500cm 2 or 6000cm 2 In a storage element with a constant rated capacity, the output of the storage element can be increased by making the facing area of the positive electrode active material layer and the negative electrode active material layer greater than the above lower limit. The upper limit of the above facing area is sometimes more preferably 9000 cm 2 , 8000cm 2 、7000cm 2 、6500cm 2 、6000cm 2 or 5500cm 2 In an electric storage element having a constant rated capacity, by setting the facing area of the positive electrode active material layer and the negative electrode active material layer to be equal to or less than the above upper limit, the capacity density can be increased.
[0090] The output of the storage element of one embodiment of the present invention is large, and it takes into account both high capacity density and large output. Therefore, the storage element can be particularly suitable for use in applications requiring both high capacity density and large output. The storage element is suitable, for example, as a power source for vehicles such as electric vehicles (EV), hybrid electric vehicles (HEV), and plug-in hybrid electric vehicles (PHEV), and is particularly suitable for use in HEVs.
[0091] The shape of the electric storage element of the present embodiment is not particularly limited, and examples thereof include cylindrical batteries, square batteries, flat batteries, coin batteries, button batteries, and the like.
[0092] Figure 1 The figure shows a storage element 1 as an example of a square battery. It should be noted that the figure is a perspective view of the inside of the container. An electrode body 2 having a positive electrode and a negative electrode wound with a separator sandwiched therebetween is contained in a square container 3. The positive electrode is electrically connected to a positive terminal 4 via a positive electrode lead 41. The negative electrode is electrically connected to a negative terminal 5 via a negative electrode lead 51.
[0093] <Electrical Storage Device> The storage element of this embodiment can be installed as a storage unit (battery module) composed of a plurality of storage elements in a power supply for vehicles such as EV, HEV, PHEV, a power supply for electronic devices such as personal computers and communication terminals, or a power supply for power storage, etc. In this case, it is sufficient to apply the technology of the present invention to at least one storage element included in the storage unit.
[0094] Figure 2An example of an electric storage device 30 is shown in which an electric storage unit 20 formed by collecting two or more electrically connected electric storage elements 1 is further collected. The electric storage device 30 may also include a bus bar (not shown) that electrically connects the two or more electric storage elements 1, a bus bar (not shown) that electrically connects the two or more electric storage units 20, etc. The electric storage unit 20 or the electric storage device 30 may also include a state monitoring device (not shown) that monitors the state of one or more electric storage elements.
[0095] <Method for Manufacturing Electric Storage Element> The manufacturing method of the storage element of the present embodiment can be appropriately selected from known methods. The manufacturing method, for example, comprises: preparing an electrode body; preparing an electrolyte; and accommodating the electrode body and the electrolyte in a container. Preparing the electrode body includes: preparing a positive electrode and a negative electrode; and forming the electrode body by stacking or winding the positive electrode and the negative electrode through a separator.
[0096] The electrolyte may be contained in the container by appropriately selecting from known methods. For example, when an electrolyte such as a non-aqueous electrolyte is used as the electrolyte, the electrolyte may be injected from an injection port formed in the container and then the injection port may be sealed.
[0097] <Other Implementation Methods> It should be noted that the storage element of the present invention is not limited to the above-mentioned embodiment, and various changes can be made within the scope of the present invention. For example, the structure of another embodiment can be added to the structure of a certain embodiment, and a part of the structure of a certain embodiment can be replaced with the structure of another embodiment or a known technology. In addition, a part of the structure of a certain embodiment can be deleted. In addition, a known technology can be added to the structure of a certain embodiment.
[0098] In the above embodiment, the case where the storage element is used as a non-aqueous electrolyte secondary battery (e.g., a lithium ion secondary battery) capable of charge and discharge is described, but the type and shape of the storage element are arbitrary. The present invention can also be applied to capacitors such as various secondary batteries, double-layer capacitors or lithium ion capacitors. The storage element of the present invention can also be applied to a storage element whose electrolyte is an electrolyte other than a non-aqueous electrolyte, that is, a storage element whose electrolyte contains water, etc.
[0099] In the above embodiment, the electrode body is described as a positive electrode and a negative electrode stacked with a separator interposed therebetween, but the electrode body may not have a separator. For example, the positive electrode and the negative electrode may be in direct contact with each other in a state where a non-conductive layer is formed on the active material layer of the positive electrode or the negative electrode. Example
[0100] Hereinafter, the present invention will be described in more detail by way of examples, but the present invention is not limited to the following examples.
[0101] [Example 1] (Production of positive electrode) LiNi is used as the positive electrode active material 1 / 3 Co 1 / 3 Mn 1 / 3 The positive electrode mixture paste is prepared by using O2, acetylene black (AB) as a conductive agent, polyvinylidene fluoride (PVDF) as a binder, and N-methylpyrrolidone (NMP) as a dispersion medium. It should be noted that the mass ratio of the positive electrode active material, AB and PVDF is 93:4:3 (solid content conversion). The positive electrode mixture paste is applied on both sides of the aluminum foil as the positive electrode substrate and dried. Then, roller pressing is performed to obtain the positive electrode. The average thickness of the positive electrode active material layer (each layer) is 28μm, and the porosity is 42%.
[0102] (Production of negative electrode) A negative electrode mixture paste is prepared by mixing solid natural graphite as a negative electrode active material, styrene-butadiene rubber (SBR) as a binder, carboxymethylcellulose ammonium (CMC-NH4) as a thickener, and water as a dispersion medium. It should be noted that the mass ratio of solid natural graphite, SBR and CMC-NH4 is 98:1:1 (solid content conversion). The negative electrode mixture paste is applied to both sides of the copper foil as the negative electrode substrate and dried. Then, roller pressing is performed to obtain a negative electrode. The porosity of solid natural graphite is 0.49%. In addition, the average thickness of the negative electrode active material layer (each layer) is 34μm and the porosity is 45%.
[0103] (Non-aqueous electrolyte) Make LiPF6 at 1.2 mol / dm 3 The concentration was dissolved in a solvent prepared by mixing ethylene carbonate and ethyl methyl carbonate at a volume ratio of 30:70 to obtain a non-aqueous electrolyte solution.
[0104] (Diaphragm) A polyolefin microporous film was used as the separator.
[0105] (Assembly of energy storage elements) The positive electrode, negative electrode and separator are used to obtain a wound electrode body. In the preparation of the electrode body, the facing area of the positive electrode active material layer and the negative electrode active material layer is 6650 cm 2 The electrode body is placed in a square container, a non-aqueous electrolyte is injected and the container is sealed. Thus, the storage element of Example 1 is obtained. For the obtained storage element, the rated capacity in the following capacity confirmation test is 4.20Ah, and the rated capacity (capacity density) per unit facing area of the positive electrode active material layer and the negative electrode active material layer is 0.63mAh / cm 2 .
[0106] [Examples 2 to 6, Comparative Example 1] Except for changing the coating mass of the positive electrode mixture paste and / or the negative electrode mixture paste per unit area, the facing area of the positive electrode active material layer and the negative electrode active material layer, and the average thickness of the positive electrode active material layer and / or the negative electrode active material layer, the same operation as in Example 1 was performed to obtain each storage element of Examples 2 to 6 and Comparative Example 1. In each storage element of Examples 2 to 6 and Comparative Example 1, the rated capacity in the following capacity confirmation test, the facing area of the positive electrode active material layer and the negative electrode active material layer, and the rated capacity per unit facing area of the positive electrode active material layer and the negative electrode active material layer (capacity density) are the values of Table 1.
[0107] [Comparative Examples 2 to 5] Each storage element of Comparative Examples 2 to 5 was obtained in the same manner as in Example 1 except that hollow natural graphite (porosity 3.68%) was used instead of solid natural graphite, and the coating mass of the positive electrode mixture paste and / or the negative electrode mixture paste per unit area, the facing area of the positive electrode active material layer and the negative electrode active material layer, and the average thickness of the positive electrode active material layer and / or the negative electrode active material layer were changed. In each storage element of Comparative Examples 2 to 5, the rated capacity in the following capacity confirmation test, the facing area of the positive electrode active material layer and the negative electrode active material layer, and the rated capacity per unit facing area of the positive electrode active material layer and the negative electrode active material layer (capacity density) are the values of Table 1. It should be noted that in Comparative Examples 4 and 5, the charging depth of the hollow graphite was adjusted to be lower than the charging depth of the solid graphite or hollow graphite of Examples 1 to 6 and Comparative Examples 1 to 3 by changing the coating mass of the positive electrode mixture paste and / or the negative electrode mixture paste.
[0108] (Capacity confirmation test) In a thermostatic chamber at 25°C, constant current charging is performed with a charging current of 1.0C and a charging end voltage of 4.10V, and then constant voltage charging is performed at 4.10V. The end condition of charging is set until the total charging time reaches 3 hours. Then, a 10-minute rest period is set. Then, constant current discharge is performed with a discharge current of 1.0C and a discharge end voltage of 2.50V. Thus, the measured discharge capacity is taken as the rated capacity. It should be noted that the charging current and the discharge current are determined based on the discharge capacity (hereinafter also referred to as "design capacity") expected according to the design of each storage element using the coating mass of the positive electrode mixture paste and the negative electrode mixture paste, the opposing area of the positive electrode active material layer and the negative electrode active material layer. The design capacity shows good consistency with the rated capacity.
[0109] (evaluate) For each storage element, constant current charging is performed at 1.0C at 25°C until the amount reaches 50% of the rated capacity, making the SOC 50%. Then, discharge at a current of 0.2C, 0.5C or 1.0C for 30 seconds respectively. After each discharge is completed, constant current charging is performed at a current of 1.0C to make the SOC 50%. The relationship between the current in each discharge and the voltage ten seconds after the start of the discharge is plotted, and the DC resistance is calculated from the slope of the straight line obtained from the plot of the three points. The output ten seconds after the start of the discharge is calculated based on the calculated DC resistance. The output of each storage element based on the output of the storage element of Comparative Example 2 is shown in Table 1. It should be noted that the current values for charging and discharging are determined based on the design capacity.
[0110] In Table 1, the rated capacity per unit facing area of the positive electrode active material layer and the negative electrode active material layer is expressed as capacity density (mAh / cm 2 In addition, Table 1 shows the capacity density (mAh / cm) as an indicator that takes into account both high capacity density and high output. 2 ) and the output (relative value: %).
[0111] [Table 1]
[0112] As shown in Table 1, solid graphite was used and the capacity density (rated capacity per unit facing area of the positive electrode active material layer and the negative electrode active material layer) was 0.59 mAh / cm 2 Above and 0.90mAh / cm 2 In each of the storage elements of Examples 1 to 6 in the following range, the output (relative value) is 95% or more, and the value of the product of the capacity density and the output (relative value) is 70 or more. Thus, each of the storage elements of Examples 1 to 6 has a large output and achieves both high capacity density and large output. On the other hand, the facing area between the positive electrode active material layer and the negative electrode active material layer was reduced, and the capacity per unit facing area (capacity density) exceeded 0.90 mAh / cm 2 The output of the storage element of Comparative Example 1 is small. In addition, in each storage element of Comparative Examples 2 to 5 using hollow graphite instead of solid graphite, the product of capacity density and output (relative value) is less than 70, and it is impossible to achieve both high capacity density and high output.
[0113] Table 2 shows the average thickness and porosity of the positive electrode active material layer (each layer) and the negative electrode active material layer (each layer) of each of the above-mentioned examples and comparative examples.
[0114] [Table 2]
[0115] The present invention can be applied to power storage elements used as power sources for electronic devices such as personal computers and communication terminals, and automobiles. Description of Reference Numerals
[0116] 1 Storage element 2 Electrode body 3 Container 4 Positive terminal 41 Positive lead 5 Negative terminal 51 Negative lead 20 Storage unit 30. Electricity storage device.
Claims
1. A storage element comprising a positive electrode having a positive electrode active material layer and a negative electrode having a negative electrode active material layer, wherein the rated capacity per unit facing area of the positive electrode active material layer and the negative electrode active material layer is 0.59 mAh / cm 2 Above and 0.90mAh / cm 2 Hereinafter, the negative electrode active material layer includes solid graphite.
2. The electric storage element according to claim 1, wherein The negative electrode active material layer has an average thickness of 20 μm or more and 60 μm or less.
3. The electric storage element according to claim 1, wherein The porosity of the negative electrode active material layer is greater than or equal to 25% and less than or equal to 50%.
4. The electric storage element according to claim 1, wherein The facing area of the positive electrode active material layer and the negative electrode active material layer is 4000 cm 2 Above and 10000cm 2 the following.
5. The electric storage element according to claim 1, wherein The rated capacity is above 3.7Ah. 6 . The power storage device according to claim 1 , which is used in a hybrid electric vehicle.
Citation Information
Patent Citations
Negative pole material for lithium battery, and lithium battery
JP2005222933A
Negative electrode for power storage device, and power storage device
JP2017069039A